Family adjustments and parental behaviour among mixed marriage families - Tan, Jo Pei (2001)
The primary purpose of the study was to determine the family adjustments and parental behaviour among mixed marriage families in Malaysia. The study also examined the association between selected factors of parental characteristics (age, sex, level of education, employment status and length of marriage), child personal characteristics (age and sex) and family contexts (number of children, family income, total household size and social support) with family adjustments (oneway selforiented, oneway spouse-oriented and mixed) as well as parental behaviour (authoritarian, authoritative and permissive). In addition, the study investigated factors that uniquely contribute to various family adjustments and parental behaviour. Sample comprised 372 mixed marriage couples with children age 5 to 12 years who were chosen purposively for the study. Data were collected by interviews based on a standardized questionnaire. Family adjustments were assessed using the 'Family Adjustment Scale' by Rozumah and Rumaya (2000), while parental behaviour was measured based on a scale by Edwards (2000). Results showed that there was almost equal distribution (oneway self-oriented=38.9%, oneway spouse-oriented=28.9% and mixed=32.2%) of types of family adjustments adopt by the respondents, with slightly more (38.9%) reporting oneway self-oriented adjustment in daily and customary activities. Majority (40.1%) of the mixed marriage parents also reported to have authoritative parental behaviour. Chi-square test of independence revealed that parent's age (X²=13.07, P≤.05), sex (X²=9.67, P≤.0.1), level of education (X²=8.55, P≤.05), employment status (X²=7.57, P≤.05) and length of marriage (X²=26.35, P≤.001) were significantly associated with family adjustments. On the other hand, education level (X²=9.37, P≤.05), employment status (X²=5.25, P≤.05) and total family income (X²=33.l7, p≤.001) were also dependent on parental behaviour. In the bivariate analyses, it was noted that parents with female target child (r=-0.18, P≤.05) and higher family income (r=0.18, P≤.05) were more self-oriented in their family adjustment. Respondents who were more educated (r=0.23, P≤.05), earned higher income (r=0.35, p≤.001) and perceived more supportive social network (r=0.28, P≤.001) were more likely to exhibit oneway spouse-oriented family adjustment.